2022 IEEE 49th Photovoltaics Specialists Conference (PVSC) 2022
DOI: 10.1109/pvsc48317.2022.9938862
|View full text |Cite
|
Sign up to set email alerts
|

Extended Accelerated Stress Testing (EAST) of Glass/Glass, Glass/Backsheet and Glass/Transparent Backsheet PV Modules: Influence of EVA and POE Encapsulants

Abstract: This report is available at no cost from the National Renewable Energy Laboratory (NREL) at www.nrel.gov/publications. U.S. Department of Energy (DOE) reports produced after 1991 and a growing number of pre-1991 documents are available free via www.OSTI.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Such UVF can be correlated to yellowing and modestly reduced short‐circuit current, 15 but the magnitude of the effect was not evaluated in this work in view of more significant degradation modes discussed below. A discussion in our sister paper concludes that the luminescing chromophores seen on the module front are associated with UV absorbers migrating from the cell‐bottom encapsulant layer during lamination 16 . Oxygen bleaching is primarily seen at the perimeter of the glass substrate modules from where oxygen can diffuse in; however, evolution of the UVF signal varies with other factors such as temperature.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Such UVF can be correlated to yellowing and modestly reduced short‐circuit current, 15 but the magnitude of the effect was not evaluated in this work in view of more significant degradation modes discussed below. A discussion in our sister paper concludes that the luminescing chromophores seen on the module front are associated with UV absorbers migrating from the cell‐bottom encapsulant layer during lamination 16 . Oxygen bleaching is primarily seen at the perimeter of the glass substrate modules from where oxygen can diffuse in; however, evolution of the UVF signal varies with other factors such as temperature.…”
Section: Resultsmentioning
confidence: 91%
“…these are 58, 80, 81, and 82. sulant layer during lamination. 16 Oxygen bleaching is primarily seen at the perimeter of the glass substrate modules from where oxygen can diffuse in; however, evolution of the UVF signal varies with other factors such as temperature. For example, the glass/glass modules exposed for 1.5 years with no thermal insulation on the back shows less evolution of fluorescence due to lower operating temperature compared with the modules with thermal insulation on the back (Figure 6).…”
Section: Encapsulant Degradationmentioning
confidence: 99%
“…Currently, 90% of bifacial modules are made of GG (glass-to-glass) structures. 131 Lately, however, GB (glass-to-backsheet) structures have been developed because there are benefits in terms of lightness, cost reduction, ease of transportation, and installation. It was also confirmed that GB structures had lower PIDs than GG structures.…”
Section: Backsheetmentioning
confidence: 99%
“…[19] In accelerated weathering experiments conducted in a laboratory setting, where various stress factors like heat, [20] humidity, [21] and UV light [22] are applied; alternatives such as TPO [23] and POE [24] have demonstrated superior optical, physical, chemical, [25] mechanical, and PID [26] performance compared to EVA. Further investigation extending from laminates [27] or glass/backsheet constructions as considered in this study to glass/transparent, glass/glass [28] and bifacial [29] (for a review on degradation in bifacial modules, cf. [30] ) constructions confirms the improvement potential underlying in devised encapsulation alternatives.…”
Section: Introductionmentioning
confidence: 99%